Pengaruh Kelebihan Berat Badan Terhadap Mobilitas Taruna Di Dalam Cockpit Cessna 172 SP Pada Praktik Terbang - Fahrian Tri Ardiyanto; Dimas Hari Cahyo; Fajar Islam; Cecilia Cecilia (Indonesia Civil Pilot Academy Banyuwagi, 2025)
This study aims to analyze the impact of being overweight on cadets' mobility within the cockpit of the Cessna 172 SP aircraft during flight practice. The background of this research is the concern that being overweight may reduce the comfort and ability of cadets to operate aircraft instruments and controls, ultimately affecting flight safety. This research employs a quantitative approach with a descriptive method. Data were collected through questionnaires distributed to cadets of the Indonesian Aviation Academy Banyuwangi who practiced flying with the Cessna 172 SP aircraft. Data analysis was conducted using validity, reliability, and regression tests. The results indicate that being overweight has a significant impact on cadet mobility within the cockpit. Overweight cadets experience limitations in movement space, comfort, and the efficiency of operating aircraft instruments. These findings support the hypothesis that being overweight can affect cadet performance in the cockpit environment. Based on the results of this study, it is recommended that aviation training institutions consider the health and fitness aspects of cadets as part of their training programs. Therefore, appropriate health and fitness standards can be established to ensure safety and efficiency in flight operations.